Reproductive behavior of dung beetles (Coleoptera: Scarabaeidae) in laboratory - Cárdenas-Castro, Estrella; Páez-Martínez, Andrés (Revista de Ciencias Agrícolas, 2017)
The dung beetles have a crucial role in the ecological balance in agroecosystems due to their importance in the cleaning of meadows and in soil fertility. The aim of this study was to determine the reproductive behavior of dung beetles in laboratory. The beetles were collected directly from cow pats in five livestock farms in Casanare foothills, Colombia. The survival, taxonomy, behavior, life cycle and reproduction rate were determined in the laboratory. The species found were: Ateuchus aeneomicans, Aphodius granarius, Aphodius sp., Dichotomius agenor, Dichotomius sp and Digitonthophagus gazella. Only A. aeneomicans survived in laboratory. Its life cycle was studied. From egg to adult it ranged between 60 to 68 days, and its reproductive rate was 0.21 individuals per week. During six months, the population of A. aeneomicans did not increase; probably laboratory conditions were not optimal.